The reimagined migrant portrait - exploring the lives of Chinese and Taiwanese minorities living in South Africa - Hsu, Tzu Ting (Centre for Film and Media Studies, 2020)
This multimedia project explores the lives of Chinese and Taiwanese migrants living in South Africa and how language, culture, community and marginalisation have come to shape their identities and to visually represent them in a way that is not prevalent in mainstream media. It uses two visual mediums – photography and video interviews – to understand these migrants’ experiences, how they perceive themselves and how they think society perceives them. Data analysis consisted of a process of coding the video interviews and structural analysis of the visuals. Rising worldwide migration has simultaneously increased the spread of diasporic communities. China’s positionality as an economic powerhouse and the influx of East Asian migrants to South Africa in recent years has shone a light on this minority population group. However, much of what is known about them tends to be through forms of mass media which perpetuates stereotypical representations. This paper draws on various literature including acculturation, diasporic communities, representation, languaging and xenophobia to explore the lives of East Asian migrants living in South Africa and search for more empowered forms of representation.